2001
DOI: 10.1111/j.1541-0072.2001.tb02098.x
|View full text |Cite
|
Sign up to set email alerts
|

State Support for Higher Education: A Political Economy Approach

Abstract: This research examines state support for higher education by first ascertaining the amount supplied and demanded of this service. The approach assumes that supply and demand occur simultaneously, and that each is affected by higher education spending policies among the states. We argue that enrollment is the most satisfactory proxy for both supply and demand. State policy is measured as expenditure effort. We estimate three time‐series equations using two‐stage least squares regression with data for the years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…2001; the United States of America (USA): Nelson 1992Nelson , 1996. Secondly, there are a number of studies with a theoretical background in economics that analyse the dynamics of education spending in international or intranational comparison (Hanushek and Rivkin 1996;Fermindez and Rogerson 1997;Ram 1995;Morgan et aL. 2001).…”
mentioning
confidence: 99%
“…2001; the United States of America (USA): Nelson 1992Nelson , 1996. Secondly, there are a number of studies with a theoretical background in economics that analyse the dynamics of education spending in international or intranational comparison (Hanushek and Rivkin 1996;Fermindez and Rogerson 1997;Ram 1995;Morgan et aL. 2001).…”
mentioning
confidence: 99%
“…For example, some researchers have found that states with high-tuition policies generally have higher out-migration rates, perhaps because higher prices drive students out of the in-state higher education market (Fenske et al 1972;Mak and Moncur 2003;Rizzo and Ehrenberg 2002;Tuckman 1970). Other explanations of changing migration patterns of college students include higher education spending policies (Mak and Moncur 2003;Morgan et al 2001), employment opportunities, potential returns on investment in education (McHugh and Morgan 1984;Tuckman 1970), and the per-capita income level in students' home state (Kyung 1996).…”
Section: Other Covariates In College Migration Analysismentioning
confidence: 94%
“…Twelve articles were found, which is not a great number considering the number of academic articles published in higher education over this period (Baird, 2006;Boon et al, 2005;Greener & Perriton, 2005;Hess et al, 2001;Morgan et al, 2001;Morley, 2005a;Ntshoe, 2003;Parascondola, 2005;Shumar, 2004;Slaughter, 2001;Thelin, 2000;Torres & Schugurensky, 2002). While this is not an exhaustive list of recent articles using a political economy approach in higher education due to the limitations of the search criteria and database, the set includes articles from a diverse group of journals and authors.…”
Section: Political Economy and Research Policymentioning
confidence: 99%
“…Rather, most of the authors used the term to describe the socio/political/economic milieu, such as Morley's concerns about a vaguely defined "changing political economy" of higher education (Morley, 2005a, p. 210). A few of the articles presented the policy process as a political economy (Baird, 2006;Morgan et al, 2001;Thelin, 2000) but they did not specifically call upon political economic theories per se. Greener and Perriton (2005) and Slaughter (2001) provided the most comprehensive overviews of political economic approaches.…”
Section: Political Economy and Research Policymentioning
confidence: 99%